The relationship between COVID-19 pandemic-related stress and meaning in life: testing the moderating effects of self-compassion and savoring. Issue 1 (2nd January 2022) - Samios, Christina; Praskova, Anna; Radlinska, Basia
ABSTRACT: Background and Objectives: The stress people experience in relation to a highly stressful event, such as the COVID-19 pandemic, can undermine their sense of meaning in life. This study examined the relationship between COVID-19 pandemic-related stress and meaning in life and whether self-compassion and savoring positive emotional experience moderated this relationship. Methods: Participants ( N  = 498) completed measures of pandemic-related stress, dimensions of meaning in life (comprehension, purpose, mattering), self-compassion (self-kindness, common humanity, mindfulness), and savoring (savoring through anticipation, savoring the moment, savoring through reminiscence). Results: Results of regression analyses showed that pandemic-related stress related to less meaning in life and that all dimensions of self-compassion and savoring (with the exception of savoring through reminiscence) related positively to a dimension of meaning in life. Only common humanity buffered the relationship between pandemic-related stress and a dimension of meaning in life (purpose) as expected. Unexpectedly, for people high on common humanity the relationship between pandemic-related stress and mattering was positive, and for people high on mindfulness, the relationship between pandemic-related stress and comprehension was negative. Conclusions: Although cross-sectional, this study's findings suggest that promoting common humanity might be important for protecting purpose and enhancing one's sense of mattering during a pandemic.